2017
DOI: 10.1007/s13311-017-0538-7
|View full text |Cite
|
Sign up to set email alerts
|

HCN Channel Targets for Novel Antidepressant Treatment

Abstract: Major depressive disorder (MDD) is a chronic and potentially life threatening illness that carries a staggering global burden. Characterized by depressed mood, MDD is often difficult to diagnose and treat owing to heterogeneity of syndrome and complex etiology. Contemporary antidepressant treatments are based on improved monoamine-based formulations from serendipitous discoveries made > 60 years ago. Novel antidepressant treatments are necessary, as roughly half of patients using available antidepressants do n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
41
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(41 citation statements)
references
References 287 publications
(392 reference statements)
0
41
0
Order By: Relevance
“…In this study, we only detected the lower level of BDNF in the Hip. Another possibility may be that when chronic stress and consequent HCN channel dysfunction desynchronize cortical networks, prefrontal control over behavior, emotion, and cognition could be affected as well 7 . In other words, different physiological functions and abnormal behavior phenotypes might be evoked consistently.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, we only detected the lower level of BDNF in the Hip. Another possibility may be that when chronic stress and consequent HCN channel dysfunction desynchronize cortical networks, prefrontal control over behavior, emotion, and cognition could be affected as well 7 . In other words, different physiological functions and abnormal behavior phenotypes might be evoked consistently.…”
Section: Discussionmentioning
confidence: 99%
“…HCN1 appears to be the most predominant isoform expressed in the hippocampus (Hip), prefrontal cortex (PFC), neocortex, and cerebellar cortex. It can be regulated by the nucleotide cyclic adenosine 3',5'-monophosphate (cAMP) and ZD7288 7 . Several studies have pointed out that selective dorsal Hip reduction of HCN1 by short hairpin RNA (shRNA) exhibits reduced behavioral despair in the forced swim test (FST) and anxiolytic effects in the open-field test (OFT) and elevated plus maze test (EPMT) 8 .…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, chemogenetic activation of VTA dopaminergic neurons results in an increased responding for sucrose in a PR schedule of reinforcement, that is, it enhances incentive motivation [60] . VTA dopaminergic neurons that project to the NAcS exhibit a large hyperpolarization-activated inward current, I h , that modulates their electrophysiological properties and firing rate [61] . This current that modulates VTA firing activity seems to be crucial for the formation of cue-reward association and motivated behaviors [ 27 , 61 ].…”
Section: Discussionmentioning
confidence: 99%
“…Recent work in several brain regions has implicated HCN channels in MDD (reviewed elsewhere [67]). In many regions outside the hippocampus, animal models pertinent to MDD have observed that loss of I h is associated with more depression-like behavior [68][69][70].…”
Section: Major Depressive Disorder (Mdd)mentioning
confidence: 99%